MIXED CONVECTION PHENOMINA AFFECTED BY RADIATION IN A HORIZONTAL RECTANGULAR DUCT WITH COCENTRIC AND ECCENTRIC CIRCULAR CORE (Journal of Engineering, 2011)
The numerical investigation has been performed to study the radiation affected steady state laminar mixed convection induced by a hot inner varied positions circular core in a horizontal rectangular channel for a fully developed flow. To examine the effects of thermal radiation on thermo fluid dynamics behavior in the eccentric geometry channel, the generalized body fitted co-ordinate system is introduced while the finite difference method is used for solving the radiative transport equation. The governing equations which used are continuity, momentum and energy equations. These equations are normalized and solved using the Vorticity-Stream function. After validating numerical results for the case without radiation, the detailed radiation effect is discussed. From the parametric study, the Nusselt number (Nu) distributions in steady state were obtained for Aspect Ratio AR (0.55-1) and Geometry Ratio GR (0.1-0.9). The fluid Prandtl number is 0.7, Rayleigh number (0 ≤ Ra ≤ 104), Reynolds number Re (1-2000), Optical Thickness (0 ≤ t ≤ 10), Conduction-Radiation parameter (0 ≤ N ≤ 100) for the range of parameters considered. It is indicated in the results that heat transfer from the surface of the circular core exceeds that of the rectangle duct and when circular core is lower than the center of the channel, the rate of heat transfer decreased. The correlation equations are concluded to describe the radiation effect.